2009
DOI: 10.1002/jcb.22192
|View full text |Cite
|
Sign up to set email alerts
|

Direct inhibitory and indirect stimulatory effects of RAGE ligand S100 on sRANKL‐induced osteoclastogenesis

Abstract: Diabetes results in increased fracture risk, and advance glycation endproducts (AGEs) have been implicated in this pathophysiology. S100 proteins are ligands for the receptor of AGEs (RAGE). An intracellular role of the S100 family member S100A4 (Mts1) to suppress mineralization has been described in pre-osteoblastic MC3T3-E1 cells. However, S100 proteins could have additional effects on bone. The goal of the current study was to determine effects of increased extracellular S100 on osteoclastogenesis. We first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…Its expression is decreased during osteoblast maturation and mineralization; Reduced S100A4 synthesis leads to increased in vitro bone nodule formation (6768). It is also reported that S100A4 directly inhibit osteoclast differentiation, possibly through its induction of osteoblast production of soluble RAGE (69). In addition to S100A4, S100A6 is found to be increased in osteosarcoma (70).…”
Section: Discussionmentioning
confidence: 99%
“…Its expression is decreased during osteoblast maturation and mineralization; Reduced S100A4 synthesis leads to increased in vitro bone nodule formation (6768). It is also reported that S100A4 directly inhibit osteoclast differentiation, possibly through its induction of osteoblast production of soluble RAGE (69). In addition to S100A4, S100A6 is found to be increased in osteosarcoma (70).…”
Section: Discussionmentioning
confidence: 99%
“…We thus have further investigated functions of RAGE ligands in OC differentiation and activation, and have demonstrated that HMGB1, a proinflammatory cytokine once released from activated macrophages, promotes RANKL induced OC differentiation in a RAGE dependent manner (28). RAGE ligands, AGE and S100, are also found to be involved in regulating osteoclast differentiation directly or indirectly (29,30). However, the function of Aβ in OC differentiation and activation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between the AGEs and RAGE result in the dysfunction of immune cells 6,7) and functional alterations of various cells 8,9) , causing cytokine imbalance associated with inflammatory cytokine increases 10,11) . Furthermore, hyperglycemia shifts the balance of the RANKL/OPG interaction in the direction of tissue destruction through AGEs/RAGE interaction 33,34) . This study also indicated that the level of bone resorption due to experimental periodontitis was prominent in rats with diabetes mellitus when compared to that in normal rats.…”
Section: Discussionmentioning
confidence: 99%